The rationale behind updates to ambient ozone guidelines and standards - Xue, Kaibing; Zhang, Xin (Frontiers in Public Health, 2023)
Although air quality has gradually improved in recent years, as shown by the decrease in PM2.5 concentration, the problem of rising ambient ozone has become increasingly serious. To reduce hazards to human health and environmental welfare exposure to ozone, scientists and government regulators have developed ozone guidelines and standards. These answer the questions of which levels of exposure are hazardous to human health and the environment, and how can ambient ozone exposure be guaranteed, respectively. So what are the basis for the ozone guidelines and standards? This paper reviews in detail the process of revising ozone guidelines and standards by the World Health Organization (WHO) and the United States Environmental Protection Agency (EPA). The present study attempts to explore and analyze the scientific basis and empirical methods for updating guidelines and standards, in a view to guide the future revision process and provide directions for further scientific research. We found many epidemiological and toxicological studies and exposure-response relationships provided strong support for developing and revising the ozone guidelines. When setting standards, ozone exposure has been effectively considered, and the economic costs, health, and indirect economic benefits of standard compliance were reasonably estimated. Accordingly, epidemiological and toxicological studies and the establishment of exposure-response relationships, as well as exposure and risk assessment and benefit-cost estimates of standards compliance should be strengthened for the further update of guidelines and standards. In addition, with the increasing prominence of combined air pollution led by ozone and PM2.5, more joint exposure scientific research related to ozone guidelines and standards should be undertaken.